Police officers’ perceptions of citizens and support for procedural justice policing: the mediating roles of identity and self-legitimacy - Pass, Michael (Policing and society, 2026)
Procedural justice policing has won the interest of many police organisations who seek to improve police-community interactions and relationships. While this organisational support is invaluable for fostering procedural justice among the ranks, the success of implementation relies on buy-in from frontline officers who are expected to use procedural justice in their community interactions. Prior research suggests officers' perceptions of the public's support for police may affect their own support for, and use of, procedural justice. This article explores whether police officers’ perceiving their community as supportive of police is related to officers’ support for procedural justice. Furthermore, it draws on psychological concepts of identity formation to offer and test two mechanisms for explaining this relationship. Specifically, the study tests whether officers’ self-legitimacy and identification with their community each mediate (explain) this relationship. Drawing on survey data from 306 Australian police officers, we find that officers’ belief that the public are supportive of police predicts officers’ greater support for procedural justice. We also find that officers’ perceived self-legitimacy and identification with their community simultaneously mediate this relationship. We discuss the implications of these findings for both theory and police practice.